Synthesis of a potential angiogenesis inhibitor compound: 2-benzylidene cyclohexane-1,3-dione - Istyastono, Enade Perdana; Yuniarti, Nunung; ., Jumina (Indonesian Journal of Pharmacy, 2009)
Synthesis of an aromatic cyclic enadione, 2-benzylidene-cyclohexane-1,3-dione (a potential angiogenesis inhibitor), has been done using benzaldehide (50 mmole) and cyclohexane-1,3-dione (50 mmole) as starting materials and NaOH 1.0 N as a catalyst. Odorless and white needle-shape powder has been achieved. The powder was 252.7 mg (2.53 %) and the purity of the powder was 88.81 %. Its melting point was 214.8 oC. The purity of the product was examined by gas chromatography, while the structure elucidation was done using IR spectrometer, 1H-NMR spectrometer, and GC-MS.IR spectrometer showed that the compound had a -C=O bond conjugated to an alkene or a phenyl moiety, methylen groups, and alkene’s -C–H bonds. 1H-NMR spectrometer showed that the compound had benzene moiety and methylen moieties, which were in α and β position to a carbonyl group. GC-MS showed that the molecular weight of the compound was 200 atomic mass unit.Key words: Angiogenesis inhibitor, synthesis, 2-benzylidene-cyclohexane-1,3-dione.